Use of levetiracetam in pediatric refractory status epilepticus - Shakya, Kashyap Narsingh; Bhatta, Anwesh; Phuyal, Samjhana; Yadav, Arbind (Journal of Kathmandu Medical College, 2019)
Refractory status epilepticus, with persistence of seizures despite initial intravenous benzodiazepine and one secondline intravenous antiepileptic drug occurs in nine percent to 44% of the patients with status epilepticus. Aggressive treatment is needed to control such seizures with drug refractoriness. A case of a 2-year-old boy treated with intravenous levetiracetam with cessation of seizures, averting the need for general anesthesia is reported. Option of using levetiracetam in refractory status epilepticus is suggested.